2018
DOI: 10.1186/s40494-018-0174-5
|View full text |Cite
|
Sign up to set email alerts
|

Colour identification, degradation processes and findings in a fifteenth-century Book of Hours: the case study of Cofre n.º 31 from Mafra National Palace

Abstract: This paper presents the work done as part of a master dissertation on Conservation and Restoration at the Faculty of Sciences and Technology, Nova University of Lisbon. The "Cofre n.º 31" is a French fifteenth century Book of Hours from the Library of the National Palace of Mafra, Portugal. This prayer book, composed by illuminations and devotional texts, was in bad condition due mainly to the rebinding done between eighteenth and nineteenth centuries. According to the assessment of the state of conservation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In heritage science, there is demand for noninvasive and nondestructive techniques for determination of chemically specific data regarding composition and condition of cultural and historical artifacts . Proper characterization and identification of pure and mixed colorants in these artifacts are crucial steps in determining provenance and designing appropriate protocols for conservation and restoration efforts. Various approaches for pigment identification are currently employed and include X-ray fluorescence spectroscopy and secondary-ion mass spectrometry, as well as near-infrared (near-IR), mid-IR, and Raman spectroscopies. However, low-frequency vibrational spectroscopies that access ≤200 cm –1 (≤6 THz) vibrational motions in solid samples have attracted great attention in recent years. Terahertz time-domain spectroscopy (THz-TDS) and low-frequency Raman spectroscopy (LFRS) are appealing methods for in situ studies of artifacts because of their specificities, acquisition times, and nondestructive approaches. The utilization of these emerging techniques has been driven largely by improvements in instrumentation capabilities and costs, , and advances in the quantum mechanical solid-state simulations used to assign and interpret the spectral data. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In heritage science, there is demand for noninvasive and nondestructive techniques for determination of chemically specific data regarding composition and condition of cultural and historical artifacts . Proper characterization and identification of pure and mixed colorants in these artifacts are crucial steps in determining provenance and designing appropriate protocols for conservation and restoration efforts. Various approaches for pigment identification are currently employed and include X-ray fluorescence spectroscopy and secondary-ion mass spectrometry, as well as near-infrared (near-IR), mid-IR, and Raman spectroscopies. However, low-frequency vibrational spectroscopies that access ≤200 cm –1 (≤6 THz) vibrational motions in solid samples have attracted great attention in recent years. Terahertz time-domain spectroscopy (THz-TDS) and low-frequency Raman spectroscopy (LFRS) are appealing methods for in situ studies of artifacts because of their specificities, acquisition times, and nondestructive approaches. The utilization of these emerging techniques has been driven largely by improvements in instrumentation capabilities and costs, , and advances in the quantum mechanical solid-state simulations used to assign and interpret the spectral data. , …”
mentioning
confidence: 99%
“…In this work, the focus is on the ancient pigments minium (Pb 3 O 4 ) and vermilion (HgS) because of their frequent use together in artists’ palettes and their visual similarity (see Figure ) necessitating analytical evaluation for quantification. ,,, Previous terahertz , and Raman studies have reported the spectra of pure minium and vermilion, while mixtures of the two have been studied using other techniques including midrange Raman spectroscopy and first-derivative reflectance visible spectroscopy . Here, these inorganic crystalline pigments were investigated using a combination of THz-TDS, LFRS, and ss-DFT to fully characterize their sub-200 cm –1 vibrations.…”
mentioning
confidence: 99%
“…The overall lighter hue contribution could be associated with the presence of lead white, which was added to cinnabar to obtain the lighter red hue observed. Finally, the XRF of the purple/gray area (s18, Figure 8e) showed a prominent presence of Pb-based pigment(s), known to be prone to degradation towards brown and black colorations (galena, PbS) [42][43][44].…”
Section: Pigmentsmentioning
confidence: 99%
“…)-century polychrome sculptures in the porch of the main and south portals of Ferrara cathedral (Pinna et al 2020); & 14 t h -century wood ceilings of the Hall of the Abencerrages and the Hall of the Two Sisters in the Alhambra at Granada (Arjonilla et al 2019a); & 14 th -century (third quarter) wall paintings of the Dominican Monastery at Ptuj in Slovenia (Gutman et al 2014) & 15 th (also 16 th ? )-century manuscripts on parchment (for the 15 th century, see, e.g., Chaplin et al 2005;Duran et al 2014;Bonizzoni et al 2016;Carvalho et al 2018; for a 15 th /16 th -century parchment see Vanmeert et al 2018); & 15 th -to 17 th -century panel paintings on wood or walnut (for the 15 th century, see, e.g., Duval 1990, 1998;Dunkerton and Roy, 1996;Hradil et al 2007;Bersani et al 2008;Ricci et al 2004;Sodo et al 2019;Gutman Rieppi et al 2020; for the 16 th century, see, e.g., Penny et al 1996;Higgitt et al 2003;Roy et al 2004;Mottin and Laval 2004;Plazzotta et al 2006 (doubtful); Borgia et al 2007;Hradil et al 2007;Dunkerton and Howard 2009;Amadori et al 2016;Želinska et al 2018; for the 17 th century, see, e.g., Roy 1999; Olszewska-Świetlik et al 2013); & 14 th -to 17 th -century wall paintings (for the 14 th and 15 th centuries, see, e.g., Perardi et al 2003;Gutman et al 2014;Arjonilla et al 2019a;Levstik et al 2019;Pinna et al 2020; for the 17 th century, see, e.g., Vlachou-Mogire et al 2020); & 17 th -and 18 th -century oil paintings on canvas (Feller 1973;Hradil et al 2007;…”
Section: Lead-tin Yellow Types I and Iimentioning
confidence: 99%